(untitled) (Archaeologia Adriatica, 2008)
The article discusses the find of a pintadera (stamp or model) from the late Neolithic stratum (Hvar Culture) of the multilayered site of Ravlića Cave in western Herzegovina (Bosnia & Herzegovina), where systematic excavation was first performed in 1977-1979. The pintadera was discovered during the renewed excavations that began in 2008, and in stratigraphic terms, it is related to the IIB phase there (classic Hvar Culture), which is particularly characterized by painted decorations in the crusted technique. Given that the pintadera is not connected to any particularly indicative context, the question of its function, significance, and use at this site remains completely open. Taking into consideration various opinions about the use of identical finds at other sites, as well as the conceptional and artistic similarity of the decoration on the pintadera with the motifs on the painted pottery from Ravlića Cave, which because of the technique of workmanship the author considers to be entirely unsuitable for practical use, the author attributes to it the character of an object intended for special occasions, hence related to ritual activities on the part of the inhabitants of Ravlića Cave.